The Impact of Use Social Media in Communication Flow from State House to Traditional Media in Tanzania - Kaale, Kaanaeli; Mjema, Daniel (Technium Social Sciences Journal, 2025)
The media has historically obtained and disseminated government information to the public through newspapers, radio, and television. Before the advent of social media, Journalists obtained information from the State House through telegraph, telephone, fax, and in-person encounters between the President’s communication officers and journalists. Over twenty years, the State House Communications Department has enhanced its communication methods and effectively utilized social media platforms to engage with journalists and the public. However, little focus on scientific research has been done to assess the impact of social media on communication flow from Tanzania’s state house to traditional media. Therefore, the study evaluated the application of new media in the Presidential Communication Directorate in disseminating news to the mainstream media. The study used a descriptive design and mixed-methods approach, combining qualitative and quantitative methodologies. The qualitative delved into individual viewpoints on news collection using new media, while the quantitative evaluated respondents’ perspectives. The State House Communication Unit has shifted its use of social media platforms enhancing networking among journalists, providing quick information access, and being cost-effective. However, the shift has led to decreased personal communication, a decline in exclusive news, an increase in false information propagation, and the emergence of citizen journalism. Journalists should improve their social media skills to maintain high-quality media reporting. The Statehouse should enhance its 24/7 media unit operations. The study highlighted the challenges and significance of using social media for news dissemination and gathering. The study involved media professional practitioner’s and President’s communication officers who identified significance and challenges and suggested how to improve media production and contents.